Analysis of Students' Creative Problem-Solving Ability in Static Fluids: Pilot study - Elma, Elma; Samsudin, Achmad; Suhandi, Andi (Jurnal Pendidikan MIPA, 2022)
This study aims to describe the ability of creative problem solving in static fluid materials. The method used in this study is a descriptive method which was carried out at SMAN 4 Luwu, North Sulawesi. The research sample was 36 students. The research data were collected through the provision of creative problem solving tests on static fluid materials given after the learning process was carried out. The data that has been collected is then analyzed using the calculation of the average pretest and posttest and Rasch Analysis. The results of data analysis show that reviewing four indicators, namely fact finding, problem finding, idea finding, solution finding and the highest score is on the fact finding indicator with an average of 67.57 for classes that use creative problem solving. In implementing the creative problem solving learning model, it is necessary to pay attention to the time management allocated so that each implementation can be carried out properly. The creative problem solving learning model can be tested on other materials according to school conditions.Keywords: reative problem solving, static fluids, Rasch analysis.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp816-823